Profile Characteristics of Different Categories of Farmers and Farm Women in Rice (Oryza sativa L.) Growing Eco-System of Imphal Valley - Devarani, Loukham; Bandhyopadhyay, A. K. (Indian Journal of Extension Education, 2012)
In Maklang Gram Panchayat of Imphal, 76 male and 78 female rice (Oryza sativa L.) farmers were enumerated and classified based on their land-owning status as those cultivating own field, share-croppers and landless labourers. Farm-women were found to have higher mean score in risk orientation and knowledge level. Radio, television, newspaper and friends and neighbours were the most frequently used information source. Male and female farmers differ significantly in education, socio-economic status, annual income, economic motivation, risk orientation, attitude towards improved agricultural technology, utilization of personal localite sources, personal cosmopolite sources and utilization of mass media sources. The significant differences were found between the land-owning classes of male farmers in education, socio-economic status, annual income, utilization of personal cosmopolite sources, utilization of mass media sources and knowledge level. Between farm-women, significant differences were observed in socio-economic status, annual income, risk orientation, attitude towards improved agricultural technology, independency in decision making, social participation, utilization of personal localite sources, utilization of personal cosmopolite sources and utilization of mass media.
Keywords: Rice farmers; Gender; Land-owning status; Sharecroppers